2002
DOI: 10.1016/s0014-5793(02)02576-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative structural and functional analysis of cytochrome cM, cytochrome c6 and plastocyanin from the cyanobacterium Synechocystis sp. PCC 6803

Abstract: Cytochrome c M is a new c‐class photosynthetic haem protein whose physiological role is still unknown. It has been proposed previously that cytochrome c M can replace cytochrome c 6 and plastocyanin in transferring electrons between the two membrane complexes cytochrome b 6–f and photosystem I in organisms growing under stress conditions. The experimental evidence herein provided allows us to discard such a hypothesis. We report a procedure to overexpress cytochrome c M from the cyanobacterium Synechocystis sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 26 publications
(40 reference statements)
3
33
1
Order By: Relevance
“…The δ peak disappears, whereas a peak at 360 nm is observed instead. These spectral features are identical to those reported for native cytochrome c 6 purified from Synechocystis [12]. The extinction coefficient at pH 7.0 was determined to be 23 300 M −1 cm −1 at 553 nm for reduced Cyt c 6 .…”
Section: Resultssupporting
confidence: 78%
“…The δ peak disappears, whereas a peak at 360 nm is observed instead. These spectral features are identical to those reported for native cytochrome c 6 purified from Synechocystis [12]. The extinction coefficient at pH 7.0 was determined to be 23 300 M −1 cm −1 at 553 nm for reduced Cyt c 6 .…”
Section: Resultssupporting
confidence: 78%
“…10 kDa, and their midpoint redox potential values are around 350 mVat pH 7, which is in accordance with their role as electron shuttle between cytochrome b 6 f and PSI [59]. Moreover, their isoelectric Fig.…”
Section: Nc_005072 Syn6301supporting
confidence: 69%
“…Several proposals have been made to explain the fact that these two deletion mutants can survive with neither Pc nor Cyt as the double knockout mutant has never been achieved. Some authors have suggested the existence of a third (but relatively inefficient) electron donor to PSI [44,45], and it has also been proposed the formation of a supercomplex between cytochrome b 6 f and PSI to allow direct electron transfer without any redox carrier [46]. Finally, the existence of an alternative electron transfer pathway has been discussed as well [47].…”
Section: Proteomics Of Knockout Mutants For Plastocyanin and Cytochromentioning
confidence: 99%